The Mammoth Bone Dwellings of the Upper Palaeolithic Settlement of Gіntsy (Ukraine: a First Synthesis) - Iakovleva, L.; Djindjian, F. (Археологія, 2018)
The article is devoted to the first synthesis informing the location of the dwellings in the Upper Palaeolithic site Gontsy,
their size and architecture, and provides a provisional inventory of their components. There were discovered six mammoth
bone huts, five of which were revealed during the French-Ukrainian excavations in progress since 1993. For the first time,
it may be given a comprehensive reconstruction of a campsite and all the activities made by hunters during their occupation
at the site. The six mammoth bone dwellings of various dimensions are described here for the first time, for a preliminary
synthesis.
The history of the Gontsy site excavations is given. The first excavations by narrow trenches were carried out in 1873.
The first step has concerned the excavations of the mammoth bone bed (1995-2000) and the stratigraphic connections with
the dwelling area.
The description of all the dwellings is also given by the author, as well as the notes about a specific method for studying
mammoth bone dwellings. As to the author, after excavation, the study of a dwelling starts by a data acquisition phase
with a precise map per square meter with the most accurate possible archaeozoological determination of each bone. A 3D
recording by digital photogrammetry complete the manual record.
For the first time, in the history of the excavations of mammoth bone dwellings, with the method of conservation in
situ under large hangars for protection, all the archaeological layers and dwelling structures: mammoth bone dwellings,
pits, hearths, working areas, dumping areas, butchering areas, are preserved for the preparation of a future site museum in
Gontsy, open to the public.